AMBON BANANA PEEL EXTRACT GEL (Musa paradisiaca var. Sapientum (L.) Kunt) ACCELARATES OF WISTAR RATS GINGIVA WOUND HEALING - Florence Meliawaty; Rina Putri Noer Fadilah; Putri Mentari (Fakultas Kedokteran Gigi Unjani, 2021)
A wound is a cut through the anatomical structure of tissue due to an incision of a sharp-edged object. Ambon banana peel contains tannins, flavonoids, and saponins which act as an anti- inflammatory antioxidant and antibacterial properties that facilitate the wound healing process. This research attempted to know the effect of ambon banana peel gel extract (Musa paradisiaca var. Sapientum (L.) Kunt) on wound length healing of gingiva mucosa cuts in Wistar rats. The was a pure experimental study with a sample size of 30 Wistar rats divided into three groups; the treatment group was given 10% ambon banana peel gel extract. The positive control group was assigned 10% povidone-iodine, and the negative control group was given aquades. The research was conducted by making an incision on maxillary gingival mucosa 3 mm wide in the horizontal direction with a depth of 0.25 mm using blade number 11. Observations were performed on days 0, 3, 7, and 14 after treatment using a digital calliper. Data were analyzed using the Kruskal Wallis test and then the post hoc test using the Mann Whitney test (p <0.05 significant). The research results showed that the treatment group given 10% ambon banana peel gel extract had a significant difference with a p-value <0.05 compared to the positive and negative control groups on days 3, 7, and 14. The research shows 10%. The concentration of ambon banana peel gel extract affects the accelerating wound healing process in the gingiva mucosa of Wistar rats. DOI : 10.54052/jhds.v1n1.p89-99